The first hostage : a J. B. Collins novel - Rosenberg, Joel C., 1967- (Tyndale House Publishers, Inc., 2015)
"WIth these words, New York Times journalist J. B. Collins-- reporting from the scene of a devastating attack by ISIS terrorists on an Arab-Israeli peace summit in Amman- puts the entire world on high alert. Israel and Palestinian leaders are critically injured, Jordan's king is fighting for the very existence of his kingdom. And the U.S. president is missing and presumed captured. As the U.S. government faces a constitutional crisis and Collins himself becomes a wanted man, he finds in the thick of the hunt for the president. Can the leader of the free world be rescued before the leaders of ISIS commit genocide to usher in the global reigh of their Islamic messiah? Tje fate of the world may depend on it."--Jacket.